Original paperSevere dysplasia can be distinguished from moderate and mild dysplasia of bronchial mucosa by changes in Ki-67 index - Mijović, Žaklina; Mihailović, Dragan (Polish Journal of Pathology, 2015)
Preneoplastic lesions on small bronchial biopsy specimens may cause a diagnostic dilemma. The aim of this study was to estimate karyometric variables and the Ki-67 index of preneoplastic bronchial lesions and squamous cell carcinoma of the lung. The study was performed on endoscopic samples of squamous cell carcinoma (n = 22), normal appearing mucosa surrounding carcinoma (n = 10), bronchial dysplasia of mild (n = 7), moderate (n = 6), and severe grade (n = 6), carcinoma in situ (n = 17), and normal mucosa from patients with chronic bronchitis (n = 26). Karyometric analysis was done using the image analyzer ImageJ 1.47q. Ki-67 activity was also quantified by ImageJ 1.47q with the plugin Cell Counter. The highest values of nuclear area were found in squamous cell carcinoma, and differences were statistically significant compared to normal mucosa, all grades of dysplasia and normal appearing mucosa surrounding carcinoma (p < 0.01). The Ki-67 index was significantly higher in squamous cell lung carcinoma compared to normal mucosa, mild and moderate dysplasia and normal appearing mucosa surrounding carcinoma (p < 0.01). The Ki-67 index was significantly higher in severe dysplasia than in mild and moderate dysplasia (p < 0.01). In conclusion, the Ki-67 index is a useful parameter for more objective grading and can be of prognostic value to determine the biological potential of preneoplastic bronchial lesions.